Cavitation Prevention for Submarine Propeller with Empirical Method - Prihandanu, Riyan Bagus; Baidowi, Achmad (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
Submarines are a component that is taken into account in assessing the security of a country. Many countries have developed their own types of submarines according to technological developments in that country. To be able to move silently underwater, the most important requirement for submarine propellers is low noise generated by these propellers. So the first thing that must be avoided from the emergence of a noise on a submarine is the absence of cavitation when the propeller operates both on the surface and at depth. The cavitation value can be predicted based on the limits from the burril cavitation diagram. The diagram is obtained from cavitation experiments and recorded full-scale cavitation observations over many years. Simulation calculations will be varied by value of P/D, Ae/Ao, Number of blades (Z) and diameter (D). Other components such as advance velocity (Va) and rotation speed (n) of propeller are considered constant or ignored as in Keller's Formula. From the calculation, by adding the expanded area ratio and propeller diameter values can reduce cavitation in the propeller. While the opposite happens, when the propeller pitch value and the number of blades increase, the cavitation value will also increase. If submarine in dive condition the cavitation difficult to appears, because the pressure of the ship when diving conditions will be very high and the cavitation number will be very small.